THE ROLE OF MOTIVATION AND DIGITAL TECHNOLOGY IN ENHANCING MANDARIN LANGUAGE PROFICIENCY AMONG STUDENTS OF THE MANDARIN LANGUAGE FOR BUSINESS AND PROFESSIONAL COMMUNICATION PROGRAM AT UNPRI - Manalu, Tetti S.Y.; Vic Nixson; Lisa, Mei; Hualangi, Cynthia (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2025)
The aim of this study is to examine the extent to which motivation and digital technology influence the improvement of Mandarin language proficiency among students in the Mandarin Language for Business and Professional Communication Study Program at Universitas Prima Indonesia. Specifically, this research analyzes the effect of motivation on language mastery, the role of technology in the learning process, and the combined impact of both factors on learning outcomes. A quantitative descriptive approach was employed, with data collected through a questionnaire as the main instrument, completed by 37 respondents. The findings indicate that motivation has a significant impact on Mandarin language proficiency (significance value < 0.05; t-value = 4.390 > t-table = 2.032). In contrast, the individual use of digital technology does not have a significant effect (significance = 0.983 > 0.05). However, the integration of motivation and technology demonstrates a significant simultaneous effect (significance < 0.05; F-value = 76.279 > F-table = 3.27). These findings emphasize the importance of motivation in language learning and highlight the potential of technology when appropriately applied. Therefore, educational institutions are encouraged to develop learning approaches that combine these two aspects to enhance Mandarin language mastery.